Sub-stratum strategies in Internet advertising - Cheong, Yin Mei Cecilia (Journal of Modern Languages, 2008)
New developments in the internet have made it an effective media and source for advertising that can reach the global market quickly As a result, websites have mushroomed globally overnight to tap the overseas markets for the products advertised. Most webpages in the Internet are in English because it is regarded as an International language. In addition, English is widely used in Business CommunJcation. However, not all websites undergo meticulous translation, editing and proofreading in presenting clear information and content. As a result, many web pages have badly presented language and content. This study analyzes the use of non-standard English Language or errors in Internet advertising. It identifies errors in discourse, grammar and lexis. Errors made in advertisements, especiaHy as a result of cross-linguistic influence, should be looked into seriously as they would affect the confidence of the potential customers or clients towards a particular product or service.